2014
DOI: 10.1371/journal.pone.0089675
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Primary Ciliary Dyskinesia Epithelial Cells at Air-Liquid Interface Can Alter Ciliary Phenotype but Remains a Robust and Informative Diagnostic Aid

Abstract: BackgroundThe diagnosis of primary ciliary dyskinesia (PCD) requires the analysis of ciliary function and ultrastructure. Diagnosis can be complicated by secondary effects on cilia such as damage during sampling, local inflammation or recent infection. To differentiate primary from secondary abnormalities, re-analysis of cilia following culture and re-differentiation of epithelial cells at an air-liquid interface (ALI) aids the diagnosis of PCD. However changes in ciliary beat pattern of cilia following epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
118
2
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 23 publications
4
118
2
12
Order By: Relevance
“…Moreover, abnormal ciliary function can be secondary to infectious or inflammatory damage to the native tissue before biopsy or to damage during biopsy or mishandling of the sample prior to recording of HVMA. Repeat testing or reanalysis following culture at the air-liquid interface (ALI) [18] or under submerged conditions [19] has, therefore, been recommended [4] to confirm primary rather than secondary defects. Most defects of ciliary ultrastructure defined in adequate numbers of cilia with good preparation and sampling of images have 100% specificity; however, analysis of cilia by TEM will miss the 30% of patients who do not have ''hallmark'' ultrastructural defects [20].…”
Section: Evolution Of Diagnostic Testingmentioning
confidence: 99%
“…Moreover, abnormal ciliary function can be secondary to infectious or inflammatory damage to the native tissue before biopsy or to damage during biopsy or mishandling of the sample prior to recording of HVMA. Repeat testing or reanalysis following culture at the air-liquid interface (ALI) [18] or under submerged conditions [19] has, therefore, been recommended [4] to confirm primary rather than secondary defects. Most defects of ciliary ultrastructure defined in adequate numbers of cilia with good preparation and sampling of images have 100% specificity; however, analysis of cilia by TEM will miss the 30% of patients who do not have ''hallmark'' ultrastructural defects [20].…”
Section: Evolution Of Diagnostic Testingmentioning
confidence: 99%
“…This removes the need to repeat nasal brushing to obtain a sample for reanalysis which is required if diagnosis depends on HVMA. The ciliary phenotype changes following cell culture helping to differentiate primary from secondary dyskinesia and this change is therefore advantageous [99]. Jorissen et al [57] first reported the use of cell culture to aid PCD diagnosis using a submerged method (monolayer-suspension cell culture).…”
Section: Genetics: Pcd Is Generally An Autosomal Recessive Disease Tmentioning
confidence: 99%
“…Jorissen et al [57] first reported the use of cell culture to aid PCD diagnosis using a submerged method (monolayer-suspension cell culture). Culture followed by ciliation at air-liquid interface (ALI) [99][100][101] has the advantage of yielding more cells and cilia than the submerged method. Both submerged and ALI-culture techniques allow reanalysis by HVMA [57,99,101] and TEM [99,101,102] aiding the diagnosis of PCD.…”
Section: Genetics: Pcd Is Generally An Autosomal Recessive Disease Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The UK PCD reference centres regularly audit each other's analyses, and discuss difficult cases [6]. We routinely analyse de novo cilia following culture of the original sample at air liquid interface allowing us to differentiate primary and secondary functional and structural defects [7]. These methods are technically demanding and not available in many centres.…”
mentioning
confidence: 99%